1985
DOI: 10.1111/j.1468-5957.1985.tb00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and Its Relationship to Investment and Financing Policies: Empirical Evidence

Abstract: INTRODUCTIONEver since the publication of Miller and Modigliani's 1961 paper, dividend policy has been a controversial topic in the literature of finance. This paper presents empirical evidence relevant to one area of the controversy, the relationship between dividend, investment and financing decisions. The empirical evidence is based upon the results of a questionnaire survey which was used to elicit senior managers' perceptions of the dividend policies of 93 large Australian companies.' Previous research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
4

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
0
21
0
4
Order By: Relevance
“…Besides of the support of Miller and Modigliani, different researchers, for example, Baker et al (1985), Partington (1985), Siddiqui (1995) and Baker and Powell (1999) rejected this hypothesis showing dividends as a significant factor when investors make investment decisions in stocks. Stocks are considered to be hedge against inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides of the support of Miller and Modigliani, different researchers, for example, Baker et al (1985), Partington (1985), Siddiqui (1995) and Baker and Powell (1999) rejected this hypothesis showing dividends as a significant factor when investors make investment decisions in stocks. Stocks are considered to be hedge against inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interdependence hypothesis reflects the simultaneous equation financial decision modeling work of Dhrymes and Kurz (1967) and Partington (1985). They find dependencies that violate the separation principle.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The estimation results based on an unbalanced panel set of French firms showed that firms had a steady dividend policy. The analysis of a questionnaire [originally analyzed by Partington (1985)] about the motives for paying dividends showed that dividends were fixed on a nonresidual basis. The desire to satisfy shareholders and support the share price, and the desire to indicate future profitability, appeared to be the primary motivations for paying dividends.…”
Section: The Theoretical Modelmentioning
confidence: 99%